Smart Remote To Projector System: Alat Bantu Presentasi Wireless untuk PC dan Smartphone - Subekti, Fajar; Sulistiyo, Wahyu; Yudantoro, Tri Raharjo; Lestari, Anissa (Teknik Elektro - Politeknik Negeri Semarang, 2018)
Presentation is an active activity in which a speaker communicates ideas and information to a group of audiences. The main problem in delivering the material with presentation method using LCD projector is the excessive use of cables reducing the tidiness. The aim of this research is to develop Smart Remote to Projector System as a system of wireless presentation tools by utilizing Raspberry Pi for PC and smartphone. The method involves design, preparation tools and components, system development, and Testing. This system uses Raspberry Pi as access point, VNC as remote desktop, LCD projector as optical tool for projecting images, as well as PC and Smartphone as navigation. The result shows that the system is able to convey presentation data in multi display wireless at the same time using LCD projector and Raspberry Pi 3 model B. Other testing that is done using questionnaire method obtains the user satisfaction level of Smart Remote to Projector System equal to 76% from 10 respondents which mean that user satisfied with this system.Keywords : Raspberry Pi, PC, Smartphone, Multi display